Can communication training for parents of young children with movement disorders improve the communication between children and parents? A Cochrane Review summary with commentary. - Levack, William (NeuroRehabilitation, 2020)
BACKGROUND: Communication impairments are a common challenge for children with non-progressive motor disorders and their parents. OBJECTIVE: To assess the effects of parent-mediated communication interventions for improving the communication skills of preschool children with non-progressive motor disorders. METHODS: To summarize a rehabilitation-relevant Cochrane Review conducted by Pennington et al. RESULTS: Two studies were identified, involving 38 children and their mothers. These studies provided very low quality evidence that parent-mediated communication might improve parental responsiveness to their children's communication efforts, but no evidence it influence the children's communication or participation. Small samples sizes, low study numbers, and lack of reporting on some outcomes limited the conclusion that could be drawn from this review. CONCLUSIONS: High quality adequately powered trials of parent-mediate communication interventions for children with communication impairments arising from non-progressive motor disorders should be encouraged.